Obesity is associated with shorter telomere length in prostate stromal cells in men with aggressive prostate cancer - Joshu, Corinne E (Cancer Prev Res (Phila), 2020)
In our prior studies, obesity was associated with shorter telomeres in prostate cancer associated stromal cells (CAS), and shorter CAS telomeres were associated with an increased risk of prostate cancer death. To determine if the association between obesity and shorter CAS telomeres is replicable, we conducted a pooled analysis of 790 men who were surgically treated for prostate cancer, whose tissue samples were arrayed on five tissue microarray (TMA) sets. Telomere signal was measured using a quantitative telomere-specific FISH assay and normalized to DAPI for 351 CAS cells (mean) per man; men were assigned their median value. Weight and height at surgery, collected via questionnaire or medical record, were used to calculate body mass index (BMI; kg/m(2)) and categorize men as normal (<25), overweight (25≤BMI<30), or obese (≥30). Analyses were stratified by grade and stage. Men were divided into tertiles of TMA- (overall) or TMA- and disease aggressiveness- (stratified) specific distributions; short CAS telomere status was defined by the bottom two tertiles. We used generalized linear mixed models to estimate the association between obesity and short CAS telomeres, adjusting for age, race, TMA set, pathologic stage and grade. Obesity was not associated with short CAS telomeres overall, or among men with non-aggressive disease. Among men with aggressive disease (Gleason≥4+3 and stage>T2), obese men had a 3-fold increased odds of short CAS telomeres (OR: 3.06, 95%CI: 1.07–8.75; P-trend=0.045) when compared to normal weight men. Telomere shortening in prostate stromal cells may be one mechanism through which lifestyle influences lethal prostate carcinogenesis.